Solubilization, amino acid composition and electrophoretic characterization of conophor nut (Tetracarpidium conophorum)proteins - Gbadamosi, S. O.; Abiose, S. H.; Aluko, R. E.
Defatted flour was prepared from whole conophor nut by cold (4°)acetone extraction. Albumins and globulins were subsequently prepared from the defatted flour by salt extraction. Effects of solubilizing agents and pH on protein solubility were evaluated. Amino acid composition and electrophoretic properties of the flour and protein fractions were also determined. Among the several solubilizing agents tested, the most effective protein solubilizer was 0.1 M NaOH and the least effective was distilled deionized water. Conophor proteins were least soluble at pH 6 and were comprised mostly of globulins (59.50 per cent)and glutelins (33.82 per cent)fractions. The salt extract was separated into true albumins (41.86 per cent)and true globulins (58.14 per cent). Hydrophobic amino acids dominated the amino acid composition of both true albumins and globulins fractions while histidine was found to be the limiting amino acid. Total proteins and globulins were dominated by two polypeptides with estimated molecular weights (MWs)of 31 200 and 59 600. True albumins were composed of only one major polypeptide with estimated molecular weight of 31 200.
Keywords: AMINO ACID COMPOSITION; CONOPHOR NUT; ELECTROPHORESIS; PROTEIN FRACTIONATION; SOLUBILITY